Perilaku Burung Beo Alor di Penangkaran Oilsonbai, Nusa Tenggara Timur - Mariana Takandjandji; Matilde Mite (Buletin Plasma Nutfah, 2008)
Myna bird (Gracula religiosa mertensi Rensch 1928) is one of the natural resources richness of the Alor Island in East Nusa Tenggara. The bird has an important source of economic values of the local people. However, the bird population rapidly decreases each year. Today, the bird is hardly found in the native habitat. Therefore, the conservations of the bird and its habitat are highly needed. The objective of this study was to determine the behaviour of Alor’s Myna in captivity breeding of Oilsonbai, East Nusa Tenggara, and to establish the breeding system in line with the ex situ conservation program. The study was using four birds. The daily behaviour of bird is the main parameter concerned in this study. The results showed that there were identified 13 daily activities of the Myna, and can be classified into three main behaviours. The main bird behaviours were motionless, movements, and ingested. The motionless behaviours include rest, stationary, and action of drying in the sun. The activities of movements were going through certain activities, walking, climbing, visiting, flying, cleanliness of the body/mopping up activities, hanging on to the wire, and whistling. The ingested actions cover food consuming, drinking, defecation, and urinate. The analysis showed that frequency averages the movement’s behaviour about 472 times with activities average 67 times/ head/day, whereas average relative frequency about 8.2%. Frequency averages behaviour of bird ingested are 344 times with activities average 49.2 times/head/day, and average relative frequency about 6.1%. Frequency averages motionless behaviour were around 340 times with activities average 49 times/head/day and average relative frequency about 6%. AbstrakBurung beo Alor (Gracula religiosa mertensi Rensch 1928), merupakan salah satu sumber Daya alam Nusa Tenggara Timur. Burung ini mempunyai nilai ekonomi yang penting bagi masyarakat lokal. Namun populasinya telah menurun, sehingga saat ini sulit ditemukan di habitat alamnya. Oleh karena itu, pelestariannya perlu dilakukan. Tujuan penelitian ini adalah untuk mengetahui perilaku burung beo Alor di penangkaran guna menentukan sistem penangkaran yang sesuai dengan program konservasi ex situ. Pengamatan menggunakan empat ekor burung beo Alor. Hasil pengamatan menunjukkan burung beo Alor di penangkaran Oilsonbai memiliki 13 macam aktivitas harian yang digolongkan ke dalam tiga perilaku utama, yaitu perilaku diam, bergerak, dan ingestif. Perilaku diam adalah istirahat, stasioner, berjemur. Perilaku bergerak adalah jalan, memanjat, mendatangi, terbang, membersihkan diri, menggelantung, dan bersuara. Perilaku ingestif adalah makan, minum, defekasi, dan urinasi. Hasil analisis menunjukkan rata-rata frekuensi pada perilaku bergerak adalah 472 kali dengan rata-rata aktivitas 67 kali/ekor/hari, dan rata-rata frekuensi relatif 8,2%. Rata-rata frekuensi pada perilaku ingestif adalah 344 kali dengan rata-rata aktivitas 49 kali/ekor/hari, dan frekuensi relatif 6,1%. Rata-rata frekuensi perilaku diam adalah 340 kali dengan rata-rata aktivitas 49 kali/ekor/hari, dan frekuensi relatif 6%.